2020
DOI: 10.1111/psyp.13534
|View full text |Cite
|
Sign up to set email alerts
|

An ERP investigation of item‐scene incongruity at encoding on subsequent recognition

Abstract: The aim of the present study was to investigate how item‐scene incongruity at encoding influences subsequent item recognition and the associated event‐related potential (ERP) old/new effects. Participants (N = 26) studied pictures showing an item in a scene, either in a congruent condition (e.g., a tent in a field) or an incongruent condition (e.g., a shower cabin in a field). Items were presented alone at test. Behavioral data revealed a benefit of incongruent information, with greater source memory performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 61 publications
(91 reference statements)
1
7
0
Order By: Relevance
“…Specifically, congruity refers to whether the content of a target and its background information aligns with each other. ERPs studies observing this congruity effect consistently detected an N400 effect during encoding (Ganis & Kutas, 2003;Guillaume et al, 2020;Mudrik et al, 2010). Yet, the neural activity related to congruity during retrieval remains underexplored.…”
Section: Introductionmentioning
confidence: 90%
See 4 more Smart Citations
“…Specifically, congruity refers to whether the content of a target and its background information aligns with each other. ERPs studies observing this congruity effect consistently detected an N400 effect during encoding (Ganis & Kutas, 2003;Guillaume et al, 2020;Mudrik et al, 2010). Yet, the neural activity related to congruity during retrieval remains underexplored.…”
Section: Introductionmentioning
confidence: 90%
“…Previous studies have found a modulating effect of congruity on memory performance (Davis et al, 2012;Feyereisen, 2009;Guillaume et al, 2020;Ouwehand et al, 2019;Packard et al, 2020;Tibon et al, 2017;van Kesteren et al, 2013;Worthen & Marshall, 1996).…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations